Injectable 0.19-mg fluocinolone acetonide intravitreal implant for the treatment of non-infectious uveitic macular edema - Weber, Lea F. (J Ophthalmic Inflamm Infect, 2019)
BACKGROUND: A retrospective observational clinical study to evaluate the safety and effectiveness of the injectable 0.19-mg fluocinolone acetonide intravitreal implant (ILUVIEN) in the treatment of non-infectious uveitic macular edema. RESULTS: Data are presented from eight patients (11 eyes) with non-infectious uveitic macular edema who were treated with a 0.19-mg fluocinolone acetonide implant. Nine out of 11 eyes were pseudophakic prior to implantation of fluocinolone acetonide implant, and both phakic eyes required cataract surgery during the follow-up period (the median follow-up was 19 months; range, 8–42 months). Effectiveness and safety were assessed from changes in central retinal thickness (measured using spectral domain optical coherence tomography), corrected distance visual acuity, uveitic activity, and intraocular pressure. The main outcome measures were changes in central retinal thickness, corrected distance visual acuity, uveitic activity, and intraocular pressure. In 11/11 eyes, central retinal thickness improved between months 1 and 3. The mean maximum decrease of central retinal thickness throughout the follow-up period was 168 ± 202 μm (± standard deviation). Nine out of 11 eyes showed an improvement in corrected distance visual acuity (between + 1 and + 8 lines), and 2/11 eyes lost corrected distance visual acuity (− 1 and − 3 lines, respectively). Nine out of 11 eyes presented with inactive inflammation during the follow-up period, and in 1/11 eyes, there was a relapse at month 42. Four out of 11 eyes presented with a relapse of macular edema between months 3 and 8. The mean increase in intraocular pressure was 2.1 ± 4.7 mmHg. Nine eyes were pseudophakic prior to implantation of the injectable fluocinolone acetonide intravitreal implant. Both phakic patients developed a cataract that was treated with cataract surgery in the follow-up period. CONCLUSIONS: In this small case series with long-term follow-up, treatment of non-infectious uveitic macular edema with the injectable fluocinolone acetonide implant was associated with improved central retinal thickness and corrected distance visual acuity and a manageable safety profile. The advantage of this device is the long-term drug release and the fact that it can be injected into the vitreous as a minor surgical procedure, which is in contrast to other treatment options.